The right to vote / Nurul Syazwani Noh … [et al.] - Noh, Nurul Syazwani; Nazaruddin, Nur' Aifaa Zahirah; Mohammed Jamlus, Nurul Nafisya; Ahmad Kamel, Nur Shazlina (2009)
The title of this research is "Right to Vote in Malaysia". This research is done to identify the issues which cause the unsatisfactory numbers of voters in Malaysia. Recently, Malaysian has taken a pass on voting. According to statistics there's a huge number of eligible voters in Malaysia did not register as voters. There are various factors contributing to these phenomena. We need to find the best solutions in order for the democracy Malaysia alleged to have to be upheld. As Malaysia's Electoral System cannot be denied to have flaws, serious amendment should be made to the system. In the end of this research, we will come out with few suggestions for the government to cover the loopholes of the current law and policy in Malaysia's Electoral System. We hope that with the recommendations, the issues of unsatisfactory numbers of voter who are eligible to go out to vote but refused to do so can be overcome.